2016
DOI: 10.1302/2046-3758.59.2000580
|View full text |Cite
|
Sign up to set email alerts
|

Pull-out strength of cemented solidversusfenestrated pedicle screws in osteoporotic vertebrae

Abstract: ObjectivesCement augmentation of pedicle screws could be used to improve screw stability, especially in osteoporotic vertebrae. However, little is known concerning the influence of different screw types and amount of cement applied. Therefore, the aim of this biomechanical in vitro study was to evaluate the effect of cement augmentation on the screw pull-out force in osteoporotic vertebrae, comparing different pedicle screws (solid and fenestrated) and cement volumes (0 mL, 1 mL or 3 mL).Materials and MethodsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 30 publications
4
43
1
1
Order By: Relevance
“…In this case, the screws were removed again after initial placement and reimplanted after cement injection. According to our previous findings, 1 mL of cement was used in the thoracic and 3 mL in the lumbar vertebrae. Prior to mechanical testing, the cement was allowed to harden at room temperature for at least 12 h. CT scans were performed to document proper screw position.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the screws were removed again after initial placement and reimplanted after cement injection. According to our previous findings, 1 mL of cement was used in the thoracic and 3 mL in the lumbar vertebrae. Prior to mechanical testing, the cement was allowed to harden at room temperature for at least 12 h. CT scans were performed to document proper screw position.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanical pull‐out testing was performed using a material testing machine (MTS 858 Mini Bionix, Eden Prairie, MN, USA) equipped with a 25‐kN load cell. For the fixation in the testing machine, each vertebra was embedded in polymethylmethacrylate (PMMA) resin (Technovit Universal Fluid and Powder 2060, Heraeus Kulzer GmbH, Wehrheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cement augmentation of pedicle screws is increasingly used in order to improve fixation strength in osteoporotic patients [12][13][14][15]. Biomechanical studies have shown an approximately twofold increase in pull-out force and an increase in load to failure in cyclic testing by 52% for augmented pedicle screws [16][17][18][19]. However, cement augmentation of pedicle screws is associated with relevant complications such as leakage and embolism [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The primary focus has been on increasing stability by improving the side hole design of the screw (6,7), as well as the optimization of the dose of PMMA in surgery (8,9). The safety and effectiveness of CPSs have been partially con rmed in previous studies (4,5).…”
Section: Introductionmentioning
confidence: 99%